ANEMIA STATUS IN HIGH SCHOOL STUDENTS, JAMBI CITY - Maria, Ima; Aurora, Wahyu Indah Dewi; Darmawan, Armaidi; Kusdiyah, Erny; Nuriyah (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
ABSTRACTBackground: Young Woman are the most vulnerable group to experience anemia due to irondeficiency because of the period of physical growth, reproductive maturation, and cognitivetransformation that requires high levels of micro and macro nutrients, including iron. In youngwomen, anemia that lasts a long time will put the mother at risk of death, have the potential to givebirth to premature babies, and have the potential to give birth to babies with low body weight, whichare risk factors for stunting. This study will examine Hb levels in high school students in Jambi City.Methods: This study is a quantitative study with a cross-sectional design to describe anemia. Theresearch will be conducted in all Jambi City Public High Schools in August-September 2022. Thenumber of samples used in this study was 505. The sampling technique used was simple randomsampling at thirteen Public High Schools in Jambi City.Results: The study was conducted on young women in the city of Jambi who occupy high schooleducation. Of the 504 research respondents, 61 people (12.1%) had anemia, 443 people (87.9%)were normal. The median Hb level is 14.6 g/dl with a maximum value of 25.8 g/dl and a minimumvalue of <7 g/dl. Based on the regular monthly menstruation, 446 people (88.5%) admitted that theyhad regular menstruation. The number of young women who regularly consume iron tablets is 32people (6.3%). The habit of consuming tea or coffee with food was 332 people (65.9%) and the habitof consuming soda with food was 171 people (33.9%).Conclusion: High school students in Jambi City still suffer from anemia. Further intervention isneeded in giving iron tablets to adolescents and education in preventing anemia.Keywords: Anemia, Young Women